Model Arsitektur Multi-Tenant Berbasis Role-Based Access Control pada Sistem Manajemen Waralaba - Athallah, Muhammad Ifdal; Ayunda, Afifah Trista (STMIK Banjarbaru, 2026)
Franchise Management Systems (FMS) in Micro, Small, and Medium Enterprises (MSMEs) that use a multi-investor model frequently face fundamental issues such as information asymmetry and lack of accountability, mainly due to an inadequate single-owner architecture that hinders investors from validating transaction data. This research applied the Design Science Research (DSR) methodology to design a new FMS architecture model supported by three pillars: a multi-tenant architecture for data isolation, a granular Role-Based Access Control (RBAC) model for separating authority, and a database snapshotting pattern to ensure the integrity of historical data and financial reports. Functional and User Acceptance Testing (UAT) confirmed that the proposed artifact successfully provided real-time data transparency for investors, operational efficiency for branch managers, and centralized monitoring capability for central management. The main contribution of this study is the end-to-end integration of these three pillars, which is crucial for creating verified accountability within the franchise ecosystem.Keywords: Franchise Management System; Multi-Tenant Architecture; Role-Based Access Control; Data Transparency; Design Science Research. AbstrakSistem manajemen waralaba (FMS) pada UMKM dengan model multi-investor menghadapi masalah fundamental asimetri informasi dan kurangnya akuntabilitas akibat arsitektur single-owner yang tidak memadai, sehingga investor kesulitan memvalidasi data transaksi. Penelitian ini telah menerapkan metodologi Design Science Research (DSR) untuk merancang, mengimplementasikan, dan mengevaluasi sebuah artefak berupa model arsitektur FMS baru. Arsitektur ini ditopang oleh tiga pilar utama: arsitektur multi-tenant untuk isolasi data, model Role-Based Access Control (RBAC) granular untuk memisahkan wewenang, dan pola database snapshotting untuk integritas data historis. Hasil pengujian fungsional dan UAT secara konklusif memvalidasi bahwa artefak yang diusulkan berhasil menyediakan transparansi data real-time bagi investor, efisiensi operasional, dan kapabilitas pemantauan terpusat. Kontribusi utama penelitian ini adalah integrasi end-to-end dari ketiga pilar tersebut, yang krusial untuk menciptakan akuntabilitas yang terverifikasi dalam ekosistem waralaba.Kata kunci: Franchise Management System; Arsitektur Multi-Tenant; Role-Based Access Control; Transparansi Data; Design Science Research.